2020
DOI: 10.1093/europace/euaa157
|View full text |Cite
|
Sign up to set email alerts
|

Standardized pulmonary vein isolation workflow to enclose veins with contiguous lesions: the multicentre VISTAX trial

Abstract: Aims To evaluate the safety and effectiveness of pulmonary vein isolation in paroxysmal atrial fibrillation (PAF) using a standardized workflow aiming to enclose the veins with contiguous and optimized radiofrequency lesions. Methods and results This multicentre, prospective, non-randomized study was conducted at 17 European sites. Pulmonary vein isolation was guided by VISITAG SURPOINT (VS target ≥550 on the anterior wall; ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
124
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(140 citation statements)
references
References 17 publications
15
124
0
1
Order By: Relevance
“…Past studies have suggested that catheter instability often causes arrhythmia recurrences in patients undergoing AF ablation 17,18 . Although the use of a CF sensing catheter and the real‐time ablation parameters improved the ablation outcomes, 19 the stabilization of the catheter contact during the entire RF application duration is still challenging. For a stable catheter contact and durable PVI, an adjustment of the sheath position and deflection is often required 20 …”
Section: Discussionmentioning
confidence: 99%
“…Past studies have suggested that catheter instability often causes arrhythmia recurrences in patients undergoing AF ablation 17,18 . Although the use of a CF sensing catheter and the real‐time ablation parameters improved the ablation outcomes, 19 the stabilization of the catheter contact during the entire RF application duration is still challenging. For a stable catheter contact and durable PVI, an adjustment of the sheath position and deflection is often required 20 …”
Section: Discussionmentioning
confidence: 99%
“…Atrial tachyarrhythmia burden decreased from 2.68% at baseline to 0% at both one and two years, with rates of single-procedure freedom from atrial tachyarrhythmia of 87% at one year and 78% at two years, respectively. 34 Recent results of the Evaluation of AI and VISITAG™ (ABI-173) (VISTAX) 35 trial, the first multicenter prospective study (n = 340) evaluating the effectiveness and safety of CLOSE protocol-guided RFA in patients with PAF, demonstrated a high rate of first-pass isolation (82.4%) with a rate of 12-month freedom from arrhythmia close to 80% and that of 12-month freedom from repeat ablation of 90.4%, with 14 of 34 patients undergoing repeat ablation demonstrating a durable PVI lesion set. The follow-up protocol consisted of 24-hour Holter monitoring at three, six, and 12 months and weekly and symptom-driven transtelephonic monitoring.…”
Section: Ablation Index Force-time Integral and Interlesion Distancementioning
confidence: 99%
“…Im Umkehrschluss kommt es bei zirkumferenzieller Isolation der Pulmonalvenen mit einheitlichen Ablationswerten und Läsionsabstand (z.B. CLOSE-Protokoll) oder bei Kryoablation relativ selten zu ATs [9,13] (▶ Tab. 1).…”
Section: Atriale Tachykardien Nach Ablation -Mechanismen Und Klinische Manifestationunclassified